Anxiety Levels Basketball Refeeres In Java Region During Match Officiating - Satria Bayu Pamungkas; Donny Wira Yudha Kusuma (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to identify the anxiety level of C and B2 license basketball referees in Central Java Province in leading matches. The research method used was quantitative descriptive with a survey approach of 50 referees as a sample. The data collection instrument used the Sport Anxiety Scale-2 (SAS-2) questionnaire which measured three dimensions of anxiety, namely somatic, worry, and concentration disorder. The results showed that the overall anxiety level of referees was in the medium category with an average score of 29.06. Specifically, the anxiety indicator was the most dominant dimension (medium category), while somatic anxiety in the low category (1-2 years) had a higher level of anxiety compared to B2 license referees and experienced referees. The conclusion of this study is that the maturity of experience and flight hours are crucial factors in shaping the mental toughness of referees to minimize cognitive anxiety when leading matches.